Effects of Head Extension on Peak Airway Pressure During Mask-Ventilation: A Prospective, Randomized, Clinical Single-Centre Trial - Fiala, Anna; Kroess, Ruth; Neururer, Sabrina; Braun, Patrick; Nachbar, Nicole; VolkerWenzel; Paal, Peter (Annals of Anesthesiology and Critical Care, 2017)
Background: Rescuers with basic skills may have difficulties to perform efficient and safe mask ventilation. This study aimed at determining the best head position for ventilation, while avoiding stomach inflation. Methods: Forty healthy patients were mechanically ventilated with a face mask (7 mL.kg-1). The head was positioned either with n = 20 or without a cushion support (n = 20), and in three different head extension positions. Results: Head angles differed more with no cushion support at 12°; 95% CI 6 - 18°), 25° (95% CI 17 - 33°) and 32° (95% CI 27 - 37°); P < 0.05) when compared with cushion support at 5° (95% CI 3 - 7°), 16° (95% CI 13 - 20°), and 22° (95% CI 18 - 26°); P < 0.05. Without cushion support, peak airway pressure in neutral position was higher (20 cmH2O, 95% CI 17 to 23 cmH2O) than in the anesthesiologist’s favorite position (16 cmH2O, 95% CI 13 to 19 cmH2O; P = 0.000) or in extension (16 _ 7 cmH2O, 95% CI 13 to 19 cmH2O; P = 0.000). Stomach inflation correlated with body mass index in the neutral position, and in the anesthesiologist’s preferred position without cushion support. Conclusions: Our data suggested that maximal head extension with no cushion support yields the lowest and thus safest peak airway pressure during mask ventilation. Trial Registration: ClinicalTrials.govNCT01909310, registered on July 24th, 2013